The Cambridge companion to Judaism and law - Hayes, Christine Elizabeth (Cambridge companions to religion, 2017)
The Cambridge Companion to Judaism and Law explores the Jewish conception of law as an essential component of the divine-human relationship from biblical to modern times, as well as resistance to this conceptualization. It also traces the political, social, intellectual, and cultural circumstances that spawned competing Jewish approaches to its own 'divine' law and the 'non-divine' law of others, including that of the modern, secular state of Israel. Part I focuses on the emergence and development of law as an essential element of religious expression in biblical Israel and classical Judaism through the medieval period. Part II considers the ramifications for the law arising from political emancipation and the invention of Judaism as a 'religion' in the modern period. Finally, Part III traces the historical and ideological processes leading to the current configuration of religion and state in modern Israel, analysing specific conflicts between religious law and state law.